(untitled) (Iter, 2022)
The present study realices an interpretation o f the mentions o f truth in the Breviloquium o f Bonaventure. An analytic lecture o f a work that pays attention o f the foundating origine of veritas, o f her presence in the human being, created as a image and resemble o f God, but deformed by guilty. The study, as well pays attention to the splendour o f that truth in the reformed image by God and her transformed situation between return and beginning.